Adaptation of electrodes and printable gel polymer electrolytes for optimized fully organic batteries. Issue 6 (23rd February 2021) - Muench, Simon; Burges, René; Lex‐Balducci, Alexandra; Brendel, Johannes C.; Jäger, Michael; Friebe, Christian; Wild, Andreas; Schubert, Ulrich S.
Abstract: Despite intensive scientific efforts on the development of organic batteries, their full potential is still not being realized. The individual components, such as electrode materials and electrolytes, are in most cases developed independently and are not adjusted to each other. In this context, we report on the performance optimization of a full‐organic solid‐state battery system by the mutual adaptation of the electrode materials and an ionic liquid (IL)‐based gel polymer electrolyte (GPE). The formulation of the latter was designed for a one‐step manufacturing approach and can be applied directly to the electrode surface, where it is UV‐cured to yield the GPE without further post‐treatment steps. Herein, a special focus was placed on the applicability in industrial processes. A first significant capacity increase was achieved by the incorporation of the IL into the electrode composite. Furthermore, the GPE composition was adapted applying acrylate‐ and methacrylate‐based monomers and combinations thereof with the premise of a fast curing step. Furthermore, the amount of IL was varied, and all combinations were evaluated for their final performance in cells. The latter variation revealed that a high ionic conductivity is not the only determining factor for a good cell performance. Next to a sufficient conductivity, the interaction between electrode and electrolyte plays a key role for the cell performance as it enhances the accessibility of the counter ions to the redox‐active sites. Abstract :